Directed evolution engineering to improve activity of glucose dehydrogenase by increasing pocket hydrophobicity - Hua, Li; Qianqian, Bao; Jianfeng, Zhao; Yinbiao, Xu; Shengyu, Yang; Weishi, Xue; Yang, Sun; Yupeng, Liu (Frontiers in Microbiology, 2022)
Glucose dehydrogenase (GDH) is a NAD(P)+ dependent oxidoreductase, which is useful in glucose determination kits, glucose biosensors, cofactor regeneration, and biofuel cells. However, the low efficiency of the catalysis hinders the use of GDH in industrial applications. In this study, an analysis of interactions between eight GDH mutants and NADP+ is powered by AlphaFold2 and Discovery Studio 3.0. The docking results showed that more hydrogen bonds formed between mutants, such as P45A and NADP+, which indicated that these mutants had the potential for high catalytic efficiency. Subsequently, we verified all the mutants by site-directed mutagenesis. It was notable that the enzyme activity of mutant P45A was 1829 U/mg, an improvement of 28-fold compared to wild-type GDH. We predicted the hydrophobicity of the protein-ligand complexes, which was confirmed by an 8-anilino-1-naphthalenesulphonic acid fluorescent probe. The hydrophobicity index of GDH, P45A, F155Y, and N46E was 5674, 8091, 7708, and 5830, respectively, which suggested that the enzyme activity of GDH is positively related to its pocket hydrophobicity. Furthermore, P45A still showed better catalytic ability in organic solvents, reaching 692 U/mg in 10% isopropanol, which was 19-fold that of the wild-type GDH. However, its substrate affinity was affected by organic solvents. This study provides a good theoretical foundation for further improving the catalytic efficiency of GDH.